2017
DOI: 10.1111/cas.13243
|View full text |Cite
|
Sign up to set email alerts
|

NUBPL, a novel metastasis‐related gene, promotes colorectal carcinoma cell motility by inducing epithelial–mesenchymal transition

Abstract: Nucleotide binding protein‐like, NUBPL, is an assembly factor for human mitochondrial complex I, which is the biggest member of the mitochondrial respiratory chain. However, the relationship between NUBPL and carcinoma progression remains unknown. In this study, NUBPL was characterized for its role in colorectal cancer (CRC) and the underlying molecular mechanisms. Data (n = 197) from the Oncomine database revealed that mRNA levels of NUBPL were remarkably overexpressed in CRC tissues compared with normal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 19 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…EMT entails profound epigenetic and phenotypic modifications to a cell. Previous studies have reported that epithelial cells express high levels of E-cadherin, whereas mesenchymal cells express high levels of N-cadherin and vimentin ( 21 23 ). Therefore, detecting the expression level of E-cadherin, N-cadherin and vimentin has become a prevalent strategy for the verification of EMT in cells.…”
Section: Resultsmentioning
confidence: 99%
“…EMT entails profound epigenetic and phenotypic modifications to a cell. Previous studies have reported that epithelial cells express high levels of E-cadherin, whereas mesenchymal cells express high levels of N-cadherin and vimentin ( 21 23 ). Therefore, detecting the expression level of E-cadherin, N-cadherin and vimentin has become a prevalent strategy for the verification of EMT in cells.…”
Section: Resultsmentioning
confidence: 99%
“…It induces EMT, characterized by downregulation of epithelial marker (E-cadherin) and upregulation of mesenchymal markers (N-cadherin and vimentin). Moreover, it activates ERK signaling, believed to promote EMT and tumor metastasis, as inhibition of ERK suppresses the NUBPL-induced changes in EMT and cell motility [ 107 ].…”
Section: Regulation Of Emt In Colorectal Cancermentioning
confidence: 99%
“…Nucleotide binding protein-like ( NUBPL ), located on ECA1, is required for the assembly of human mitochondrial complex I, which contains 45 evolutionally conserved mitochondrial and nuclear encoded subunits. In addition to its central role for the mitochondrial respiratory chain, overexpression of NUBPL has been documented in melanoma and colorectal cancer tissue [ 34 , 35 ]. Although the effect of this gene on melanoma is still unclear, Wang et al [ 35 ] characterized NUBPL as a metastasis-related gene as they were able to show that the overexpression of NUBPL in colorectal cancer tissue was positively correlated with lymph node metastasis and advanced staging of this form of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its central role for the mitochondrial respiratory chain, overexpression of NUBPL has been documented in melanoma and colorectal cancer tissue [ 34 , 35 ]. Although the effect of this gene on melanoma is still unclear, Wang et al [ 35 ] characterized NUBPL as a metastasis-related gene as they were able to show that the overexpression of NUBPL in colorectal cancer tissue was positively correlated with lymph node metastasis and advanced staging of this form of cancer. The authors found that NUBPL induces epithelial–mesenchymal transition through the activation of ERK signaling pathway, a pathway which promotes tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%